2014
DOI: 10.1111/jnc.12712
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐dependent zinc release from intracellular ligands

Abstract: In cultured cortical and hippocampal neurons when intracellular pH drops from 6.6 to 6.1, yet unclear intracellular stores release micromolar amounts of Zn2+ into the cytosol. Mitochondria, acidic organelles, and/or intracellular ligands could release this Zn2+. Although exposure to the protonophore FCCP precludes re-loading of the mitochondria and acidic organelles with Zn2+, FCCP failed to compromise the ability of the intracellular stores to repeatedly release Zn2+. Therefore, Zn2+-releasing stores were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
(106 reference statements)
0
30
0
Order By: Relevance
“…Cytosolic free zinc levels at rest are too low to affect KCNQ channel activity (<1 nM) (12); these low levels likely explain the observation that, although TPEN reversed the augmentation of the KCNQ current by exogenous zinc, it rarely reduced the amplitude of KCNQ channels overexpressed in nonexcitable CHO cells to levels below the baseline. However, zinc can reach millimolar levels in the synaptic vesicles of neurons (13); another releasable pool of zinc is bound to intracellular proteins such as metallothioneins (15). Vesicular zinc is released during synaptic transmission and loads postsynaptic terminals through zincpermeable channels (e.g., AMPA) (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytosolic free zinc levels at rest are too low to affect KCNQ channel activity (<1 nM) (12); these low levels likely explain the observation that, although TPEN reversed the augmentation of the KCNQ current by exogenous zinc, it rarely reduced the amplitude of KCNQ channels overexpressed in nonexcitable CHO cells to levels below the baseline. However, zinc can reach millimolar levels in the synaptic vesicles of neurons (13); another releasable pool of zinc is bound to intracellular proteins such as metallothioneins (15). Vesicular zinc is released during synaptic transmission and loads postsynaptic terminals through zincpermeable channels (e.g., AMPA) (14).…”
Section: Discussionmentioning
confidence: 99%
“…Vesicular zinc is released during synaptic transmission and loads postsynaptic terminals through zincpermeable channels (e.g., AMPA) (14). Zinc also can be released from cytosolic buffers in response to acidification (15), as observed in hypoxic conditions. In a recent study FluoZin3 zinc imaging revealed large intracellular zinc transients (comparable to the rises recorded in this study in response to zinc ionophores) in hippocampal pyramidal neurons in response to oxidative stress (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neurotoxic phenomena associated with ischemia/reperfusion, such as oxidative stress and acidification, lead to Zn 2+ release from intracellular stores (Aizenman et al 2000; Sensi et al 2003). For example, a drop in intracellular pH (pH i ) below 6.5 causes Zn 2+ release from intracellular cysteine-containing ligands; yet some intracellular ligands bind Zn 2+ when pH i drops to 6.1 (Kiedrowski 2014). ATP might be one such ligand because it binds Zn 2+ (Churchich et al 1989; Nakano and McCormick 1991) and its intracellular concentration in the brain is in the millimolar range (Erecinska and Silver 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, for routine studies aimed to determine the impact of various experimental conditions on [Zn 2+ ] i , this approach is not practical. Therefore in the present work, an attempt was made to calibrate acid-induced [Zn 2+ ] i elevations using a low affinity ratiometric Zn 2+ probe, FuraZin-1, whose Zn 2+ K d at pH 6.1 is 39 μM (Kiedrowski 2014). Contrary to the previous estimates obtained using high affinity Zn 2+ probes, the data obtained using FuraZin-1 show that, upon acid-induced Zn 2+ release from intracellular stores, [Zn 2+ ] i elevates to about 2 μM.…”
Section: Introductionmentioning
confidence: 99%